Late-onset ‘sloughing esophagitis’ (esophagitis dissecans superficialis) associated with bullous pemphigoid - Morel-Cerda, Eliana Carolina (BMJ Case Rep, 2020)
Pemphigus is a rare autoimmune disease that causes blistering of the skin and oral mucosa. In bullous pemphigoid (BP), skin involvement is predominant, whereas oesophageal involvement is rare, compared with other blistering diseases. We present, herein, the case of a 67-year-old man with a history of successfully treated BP that 2 years later developed progressive dysphagia, unintentional weight loss and iron deficiency anaemia. An endoscopy with biopsies was performed, and its findings were consistent with ‘sloughing esophagitis’ (esophagitis dissecans superficialis) associated with BP. Oesophageal involvement was present during the first weeks, making our case unusual due to the isolated oesophageal symptoms that developed 24 months later.